Shenqi granule upregulates CD2AP and α-actinin4 and activates autophagy through regulation of mTOR/ULK1 pathway in MPC5 cells. (1st March 2023) - Wei, Lifeng; Yong, Jun; Zhang, Xianwen; Ling, Chunyan; Wu, Yansheng; Xu, Zheng; Zhang, Hengzhou; Cao, Xueqing; Sheng, Lingli; Zhang, Quan; Chen, Yiping; Wang, Lin
Abstract: Ethnopharmacological relevance: The incidence of membranous nephropathy (MN) continues to rise globally. Shenqi granule (SQ), composed of thirteen Chinese medicinal herbs, has clinical efficacy in the treatment of MN and has been used in China for decades. However, the mechanism behind this effect remains unclear. Aim of the study: In this study, we documented the effects of SQ on cultured mouse podocytes (MPC5) cytoskeletal proteins (CD2AP, α-actinin4) and autophagic activity, and identified the mechanism underlying the ameliorating effects of SQ on MN. Materials and methods: The main components of SQ was analysed using High-performance liquid chromatography (HPLC). We induced MPC5 cells with puromycin aminonucleoside (PAN) as a model of MN-like disease. Cyclosporine A (CsA) was used as a positive control drug. MPC5 cells viability was analysed using CCK-8 assays to select the PAN dose and SQ dose. CD2AP and α-actinin4 mRNA expression was examined by RT-PCR, CD2AP and α-actinin4 protein expression as well as autophagic activity (LC3, Beclin1) was examined by Western blot in MPC5 cells, and the mechanism of action of SQ granule was assessed by Western blot to detect the protein expression at the phosphorylation level of PI3K/AKT/mTOR pathway. Results: In PAN-induced MPC5 cells, mRNA and protein expression of α-actinin-4 and CD2AP were significantly reduced, and SQ granule was able to alleviate this manifestation. In contrast to the inhibition of LC3 and Beclin1 expression in the PAN model, SQ granule was able to activate cellular autophagic activity. In addition to this, our study revealed that PAN could activate the mTOR/ULK1 pathway, resulting in a significant increase in p-mTOR and p-ULK1 protein expression, while the SQ group was able to significantly inhibit the phosphorylation level of this pathway. Conclusions: SQ granule attenuated PAN-induced MPC5 cell damage similar to MN. The mechanism may be to upregulate the expression of α-actinin-4 and CD2AP and activate autophagy activity, which may be achieved by inhibiting the phosphorylation level of mTOR/ULK1. Graphical abstract: Image 1